Philosophy of Educational Management: The Usefulness and Benefits of Islamic Educational Management in the Development of Science - Herlin Yulianti; Abd. Muid N. (Lembaga Yasin AlSys, 2025)
Educational management faces increasingly complex challenges in meeting demands for quality, accountability, and relevance, which requires a robust philosophical foundation that provides clear value orientation and meaning for managerial practice. This study aims to examine the philosophy of Islamic educational management and its uses and benefits for the development of educational science and the practice of educational governance. Employing a qualitative approach through library research, the study reviews and analyzes relevant academic books and scholarly journal articles, with data processed using descriptive–analytical content analysis that focuses on the ontological, epistemological, and axiological dimensions of Islamic educational management. The findings indicate that Islamic educational management has distinctive characteristics grounded in the integration of revelation, reason, and empirical experience, and is oriented toward the values of monotheism, trust, justice, and public benefit. This philosophical approach broadens the paradigm of educational management from a purely technical–administrative activity into a reflective, value-based, and humanistic discipline. The study concludes that the philosophy of Islamic educational management makes a significant contribution to the development of holistic and transformative educational management science and provides practical direction for effective, ethical, and sustainable educational governance.